SOCIAL INTEGRATION THROUGH SPORT TO HEARING IMPAIRED STUDENTS - Rusu O.; Rusu D. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Introduction. The process of social integration of the individual through sporting activities is bivalent: spontaneous, and conscious. Success in various activities (school, sports, etc.) and in interpersonal communication support to the decrease of feelings of inferiority, psycho-emotional balancing, and the forming of positive self-esteem. At the level of hearing impaired students there are a number of particular issues of socio-emotional development, the specificity of personality and behavioral structures, important aspects to be considered in the process of social integration. Scope. Identifying ways and means to improve self-esteem in hearing impaired students which may facilitate their social integration. Hypothesis. We suppose sport activities in the formal educational system (school sports competitions) contribute to a greater extent to increase self-esteem of hearing impaired students compared with other activities. Methods. For this study, the Multidimensional Attitude Scale for Self-Esteem E.T.E.S. (60 items with choice Yes / No) testing performed on groups of 15 students belonging to one category in a classroom over approximately 60-70 minutes for each group (elite - with school results, sport, painting). There were included 90 students with hearing deficiencies of the vocational school at "Vasile Pavelcu" Special Technical High School in Iasi, 45 boys and 45 girls, aged between 17 and 20. Results. The subjects in the sports group have a significantly higher total self-esteem than the other two groups, and at the level of self-esteem subdivisions, significant differences in favor of the sports group are recorded in the physical self-esteem, social self-esteem and, interestingly, schoolar self-esteem. Conclusions. The present study strengthens the fact that the practice of physical and sports activities promotes the personality, offers the possibility of establishing new relationships, new forms of communication between individuals, and thus the possibility of integration into a group, regardless of the profession, occupation, level of education, culture, health condition.